2021
DOI: 10.1039/d1ma00747e
|View full text |Cite
|
Sign up to set email alerts
|

Nanoarchitectonics of metal organic frameworks and PEDOT layer-by-layer electrodes for boosting oxygen reduction reaction

Abstract: We present a strategy for the integration of three building blocks in a functional interfacial nanoarchitecture in order to fabricate composite films with improved features towards the electrochemical oxygen reduction...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 80 publications
(100 reference statements)
4
5
0
Order By: Relevance
“…From the CV curves, it can be observed that the capacitance of the electrode upon the modified-PLL clicking increases by 16%. This result is ascribed to the incorporation of the charged polyelectrolyte on the conducting polymer electrode and is in line with previous reports since the deposition of polyelectrolytes is known to increase the double-layer capacitance of conducting polymer electrodes. ,, …”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…From the CV curves, it can be observed that the capacitance of the electrode upon the modified-PLL clicking increases by 16%. This result is ascribed to the incorporation of the charged polyelectrolyte on the conducting polymer electrode and is in line with previous reports since the deposition of polyelectrolytes is known to increase the double-layer capacitance of conducting polymer electrodes. ,, …”
Section: Resultssupporting
confidence: 92%
“…23,35 In addition, CV measurements show that the deposition of the PEDOT-N 3 layer originates a significant change in the response of the conducting polymer electrodes (Figures 1C and S3), shifting from the typical capacitive-like behavior of PEDOT-based electrodes to a more resistive character. 11,46 This result can be ascribed to the lower conductivity of the azido-bearing polymer compared to that of PEDOT:TOS, in agreement with previously reported results. 18 Next, by making use of an electrolyte-gated configuration (Figure 1D), the transfer characteristics of the PEDOT:TOS OECTs before and after PEDOT-N 3 modification were evaluated.…”
Section: ■ Results and Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Regarding strategies for surface functionalization, the layer-by-layer assembly (LbL) technique appears as a straightforward approach for the deposition of macromolecules with multiple charges to form multilayers in a controlled manner . This technique was first described by Decher et al, and, although it was originally established for the construction of polyelectrolyte multilayers, nowadays it has been expanded to a great variety of materials and surfaces. When making use of the LbL technique, the alternate deposition of building blocks avoids undesirable consequences such as aggregation and allows intimate contact between the different film constituting elements, features that are crucial for efficient transport properties. , Therefore, LbL-interfacial nanoarchitectures exhibiting the integration of diverse materials into structurally stable and functional interfacial systems have received increased attention from the scientific community, showing great performance in applications related to energy storage and conversion, catalysis, and biosensing technologies. , …”
Section: Introductionmentioning
confidence: 99%